2017
DOI: 10.1007/s10722-017-0579-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of cardoon (Cynara cardunculus L.): assessing biodiversity for applications based on tradition, innovation and sustainability

Abstract: Selected cardoon cultivars established in the "Serra da Estrela" region were analysed to evaluate morphological characteristics related principally to the production of cardoon flowers, which are a compulsory ingredient for particular Mediterranean PDO cheese regions. The biodiversity of twelve cardoon cultivars installed in an experimental field were evaluated over three growing seasons using thirty-four morphological descriptors. Statistically significant differences were found between cultivars for twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…The study of morphological characteristics has shown a great biodiversity among different cardoon populations and confirmed the wide genetic variability that is a characteristic of this species [15]. The variability of thistle populations is not limited to morphological characteristics; it has also been observed in the AP content of the flowers.…”
Section: The Thistle Flower and The Impact Of Its Variability On Milksupporting
confidence: 52%
See 1 more Smart Citation
“…The study of morphological characteristics has shown a great biodiversity among different cardoon populations and confirmed the wide genetic variability that is a characteristic of this species [15]. The variability of thistle populations is not limited to morphological characteristics; it has also been observed in the AP content of the flowers.…”
Section: The Thistle Flower and The Impact Of Its Variability On Milksupporting
confidence: 52%
“…Triangles indicate glycosylation sites. Based on References[14][15][16] and UniProt KB accession Q9XFX3 and Q9XFX4.…”
mentioning
confidence: 99%
“…Innovations are also associated with the possibility to manipulate the final texture/sensory profile of Serra da Estrela cheese mainly via the thistle ecotype selected (Correia et al, ; Guiné et al, ). The genotype evaluation of selected cardoons has been performed in order to improve the quality and standardization of cardosin profiles from cardoon flowers used for cheese production (Barracosa, Rosa, Barros, & Pires, ), having the different cardoon cultivars been morphologically evaluated (Barracosa, Oliveira, Barros, & Pires, ). Other ways of innovation are the conversion of this traditional cheese into a functional food.…”
Section: Innovation Concerning Serra Da Estrela Cheesementioning
confidence: 99%
“…cardunculus L. based on morphological, biochemical and molecular analysis. Morphological studies showed differences for biomass production between cultivated and wild cardoon . There have been some studies based exclusively on the characterization of protein diversity in wild cardoon flowers .…”
Section: Introductionmentioning
confidence: 99%
“…Morphological studies showed differences for biomass production between cultivated and wild cardoon. [6] [7] There have been some studies based exclusively on the characterization of protein diversity in wild cardoon flowers. [8] [9] Lahoz et al, [10] by the combination of morphological and biochemical traits, have shown that the variability of individual bioactive compounds is dependent on specific genotypes, plant organs, environmental conditions and harvesting time.…”
Section: Introductionmentioning
confidence: 99%